THE OPTIMIZATION OF PRODUCTION ZEOLITE Y CATALYST FROM RHA BY RESPONSE SURFACE METHODOLOGY - Didi Dwi Anggoro; Aprilina Purbasari (Reaktor, 2009)
Rice husk is the milling byproduct of rice and is a major waste product of the agriculture industry. Amorphous silica, commonly referred to as rice husk ash, was extracted from rice husk by acid leaching, pyrolysis, and carbon-removing processes. These properties make the ash a valuable raw material for many industries.  This paper is study of synthesized of zeolite Y from rice husk ash. Zeolite Y synthesis is used for petroleum industry as expensive catalyst. Rice husk was calcined at temperature 700oC for two hours using furnace to produce pure silica. The composition of synthesized of zeolite Y from rice husk was 2.24 Na2O:Al2O3:8SiO2:112 H2O. The gel solution was mixed at room temperature for 24 hours using autoclave. Then, the gel solution was heated with variable temperature and time crystallization. The product zeolite synthesis Y was filtered and washed with distilled water until pH lower than ten, than dried at oven. This product was analyzed with X-Ray Diffraction (XRD). From XRD analyze result indicated that from rice husk ash can produced zeolite synthesis Y which high crystallization degree. The optimum conditions for synthesis of zeolite Y from rice husk ash are temperature at 100oC for 48 hours, silicate at 20%, and aluminate at 10%.